Pengaruh Kecepatan Rotor Dan Konsentrasi Katalis Pada Pembuatan Biodiesel Dari Cpo Dengan Reaksi Esterifikasi Menggunakan Sentrifugal Kontaktor - Gery Azhari Putera; Idral Amri; Silvia Reni Yenti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Fuel needed for diesel engines in Indonesia each year increased along with the number of industrial machinery and the amount of diesel vehicles engine. With limited oil reserves, it is necessary to look for alternative sources of energy. Centrifugal contactor technology is one of the alternative technology of biodiesel production is very likely to be developed. Therfore, we need a study of biodiesel production using palm oil feedstock and methanol as reagent and sulfuric acid as a catalyst by using the esterification reaction. And this study used centrifugal contractors as the main equipment, which is equipped with a heater, raw material tank, product tank and pumps. Fixed variables selected in this study is the reaction time of 120 minutes, the molar ratio of feed is 9:1, and 60 ° C operating temperature. While the manipulated variable is rotor speed (1200, 1800 and 2400 rpm), the concentration of sulfuric acid catalyst (5%, 10% and 15% v/v methanol). The results of the research that has been done is the characteristics of biodiesel produced in this study, the kinematic viscosity values from 2,41 to 2,51 mm2/s, density 858-863 kg/m3, and acid number 6,30 to 6,66 mg-KOH/g. The composition of the methyl ester obtained is 0,33% behenic metyl ester, 48,87% palmitic methyl ester and 50,80% oleic methyl ester. The best conversion is 56,03% at the optimum operating conditions with a catalyst concentration of sulfuric acid 10% v/v methanol and the rotor speed of 2400 rpm. Correlation of rotor speed on reaction rate constant is k = 0,0002Re(0,1928) . And the relationship of the catalyst concentration the reaction rate constant is k = 0,0055[Q] 0,089.          Keywords: CPO, Centrifugal Contactors, Biodiesel, Esterification Reaction